INTRANASAL MICROEMULGEL AS SURROGATE CARRIER TO ENHANCE LOW ORAL BIOAVAILABILITY OF SULPIRIDE - Ayoub, Abdallah Mohamed; Ibrahim, Mahmoud Mokhtar; Abdallah, Marwa Helmy; Mahdy, Mahmoud A. (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The purpose of this study is to evaluate microemulsion based gel (MBG) of sulpiride "a poorly water soluble antipsychotic with low oral bioavailability." Methods: Gelling polymers such as sodium carboxymethylcellulose (CMC-Na), hydroxyl propyl methyl cellulose (HPMC K4m), carbopol 940 and Na alginate were evaluated for their potential to gel sulpiride microemulsions (MEs) without affecting the MEs structure. Also, sulpiride solution (SS) and conventional gel (without ME) were prepared and compared with MBG. Gel formulations were checked for their viscosity, pH, spreadability (S), mucoadhesive force (MF), and nasal ciliotoxicity studies. The in vitro release of sulpiride across a cellophane membrane and its permeation through the nasal mucosa in phosphate buffered saline pH 6.8 (PBS) were also performed. In addition, a pharmacodynamic study of optimized formulae compared to SS and microemulsion (ME) was evaluated in rats. Results: CMC-Na and HPMC K4m were not able to gel sulpiride loaded MEs while Na alginate gave an unclear gel with a sticky texture. Results revealed that the viscosity, mucoadhesion force, and spreadability of the MBG increased with increasing carbopol 940 concentrations. The flux was arranged as the following, MBG>conventional gel>sulpiride solution (SS). According to histopathological study, safe and non-irritant MBGs suitable for nasal administration were successfully prepared. Finally, the pharmacodynamic study indicated that intranasal sulpiride MBG had a significant effect (*P<0.001) than SS and ME administered either intravenous or intranasal. Conclusion: MBG provides signiï¬cant enhancement in nasal bioavailability not only by absorption enhancing effect of ME but also, by increasing nasal residence time